2005
DOI: 10.1016/j.ijpsycho.2005.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Attention deficit and impulsivity: Selecting, shifting, and stopping

Abstract: The present selective review addresses attention, inhibition, and their underlying brain mechanisms, especially in relation to attention deficit/hyperactivity disorders (AD/HD), and the effects of methylphenidate. In particular, event-related potential (ERP) studies suggest a deficit in the early-filtering aspect of selective attention in children with AD/HD. Results from stop tasks are consistent with impairments in stopping performance in AD/HD, but in children (as opposed to adults) these effects cannot be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 80 publications
3
51
2
Order By: Relevance
“…Similarly, the greater amplitude observed in response to the no-go part of the test could be construed as reflecting more mature forms of inhibition control. These responses are consistent with those reported by others [41,42]. The authors suggest that their results from the ERP analyses are consistent with previous data from the same cohort in which LCPUFA-supplemented children outperformed controls in executive function tasks involving learning rules and inhibition tasks [31].…”
Section: Early Life Exposure To Dha and Ara Results In Long-term Diffsupporting
confidence: 92%
“…Similarly, the greater amplitude observed in response to the no-go part of the test could be construed as reflecting more mature forms of inhibition control. These responses are consistent with those reported by others [41,42]. The authors suggest that their results from the ERP analyses are consistent with previous data from the same cohort in which LCPUFA-supplemented children outperformed controls in executive function tasks involving learning rules and inhibition tasks [31].…”
Section: Early Life Exposure To Dha and Ara Results In Long-term Diffsupporting
confidence: 92%
“…It is possible that more consistent effects may be found in the 'processing negativity', which is the negative shift seen in a selective attention task by comparing ERPs of stimuli from the attended to those of the unattended channel, appearing in a time range covering the N1, P1 and N2 (Altenmüller and Gerloff, 1999). Recently, it has indeed been reported that ADHD patients have a reduced processing negativity in an auditory selective attention task (Jonkman et al, 1997;Kenemans et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, two substances with opposing effects on general information processing have identical effects on selectivity of attention. We have previously proposed a solution of this apparent contradiction (Kenemans et al, 2005), resting on two assumptions: clonidine (NE reduction) mainly reduces attentional control, therefore reduces the validity effect; nicotine (ACh enhancement) mainly facilitates disengagement, therefore reduces the validity effect. For a true test for this hypothesis however, it is necessary to use separate ERP correlates for attentional control and disengagement, respectively, which have indeed been described, eg, cuelocked attention-directing negativity and positivity (van der Lubbe et al, 2006) and the late-positive deflection that is larger to invalid than to valid targets (Mangun and Hillyard, 1991).…”
Section: Top-down: Selective Attentionmentioning
confidence: 99%